ANALISIS DAN PERANCANGAN WIDE AREA NETWORK (WAN) BERBASIS IP VPN PADA PT. AUTOCOMP SYSTEMS INDONESIA - Nugroho, Fauyhi; Herianto, Ricki (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this research is to analyze and design an IP VPN-based Wide Area Network (WAN) at PT. Autocomp Systems Indonesia to facilitate employees in accessing a centralized information system quickly, stably and securely. The company currently uses a Leased Line-based WAN network, but there are many disadvantages such as high costs and low bandwidth capacity. so the authors try to solve this problem. The methodology used in this research is NDLC (Network Development Life Cycle). The NDLC method consists of Analysis, Design, Simulation Prototyping, Implementation, Monitoring and Management. To design this network the author uses GNS3 simulation software (Graphical Network Simulator-3).The conclusion obtained from this study is that IP VPN-based WAN networks can reduce costs and provide higher network speeds than Leased Line-based WAN networks.